2022
DOI: 10.3390/plants11172262
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a Potyvirus Chimera Increases Its Virulence in a Compatible Host through Changes in HCPro

Abstract: A viral chimera in which the P1-HCPro bi-cistron of a plum pox virus construct (PPV-GFP) was replaced by that of potato virus Y (PVY) spread slowly systemically in Nicotiana benthamiana plants and accumulated to levels that were 5−10% those of parental PPV-GFP. We tested whether consecutive mechanical passages could increase its virulence, and found that after several passages, chimera titers rose and symptoms increased. We sequenced over half the genome of passaged chimera lineages infecting two plants. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Compared to the parental PPV-GFP, the chimera accumulated and moved poorly (Sun et al, 2022), but after several mechanical passages it increased in virulence (titres, symptoms, speed of infection) in some plants. This adaptation correlated with the detection in the viral consensus sequences of those plants of non-synonymous mutations in some cistrons, two of them inside HCPro, changing amino acid 352 (Ile→Thr) or 454 (Leu→Arg) (Sun et al, 2022). Multifunctional HCPro suppresses sRNA-based silencing defences against potyviruses and is therefore important in allowing compatible infections and in setting viral titres (Li & Wang, 2019;Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Compared to the parental PPV-GFP, the chimera accumulated and moved poorly (Sun et al, 2022), but after several mechanical passages it increased in virulence (titres, symptoms, speed of infection) in some plants. This adaptation correlated with the detection in the viral consensus sequences of those plants of non-synonymous mutations in some cistrons, two of them inside HCPro, changing amino acid 352 (Ile→Thr) or 454 (Leu→Arg) (Sun et al, 2022). Multifunctional HCPro suppresses sRNA-based silencing defences against potyviruses and is therefore important in allowing compatible infections and in setting viral titres (Li & Wang, 2019;Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…From the viral consensus sequences in those plants, adaptation correlated with the presence of either of two naturally acquired amino acid substitutions in the HCPro, the presence of substitutions in other viral proteins, such as the VPg and the coat protein (CP), or of mutations in non‐coding regions. We also found that the two amino acid substitutions inside HCPro, amino acids 352 Ile→Thr or 454 Leu→Arg, coincided with sites that displayed recurrent nucleotide polymorphisms in libraries of small RNA (sRNA) reads of viral sequences generated in first infections (Sun et al., 2022 ). This suggested that from the start of infection selective pressures were favouring within the viral population genomic copies that carried those specific mutations, in addition to limited variability elsewhere (Sun et al., 2022 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been reported as a viral suppressor. HC-Pro is required to enhance expression via the fusion of P1, symptom development, and viral replication [103][104][105][106][107][108]. Until now, the potential for exploiting the regulation of sugarcane genome-encoded miRNA to abate infection by SCMV has not been investigated as a strategy for developing tolerant or resistant sugarcane cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported as a viral suppressor. Enhanced expression by fusion of P1, symptoms development and viral replication are the key functions [61][62][63][64][65][66]. The miRanda and RNA22 algorithms predicted target site of sof-miR168 (a, b) at nucleotide position 1827.…”
Section: Sugarcane Mirnas Targeting Hc-promentioning
confidence: 99%